150 Bone mineral density and associated factors: do young female dancers and other recreational sport athletes differ?. (3rd March 2020) - Critchley, Meghan; Toomey, Clodagh; Lobos, Stacey M; Palacios-Derflingher, Luz; Kenny, Sarah J; Emery, Carolyn
Abstract : Background: As an aesthetic activity, dancers are susceptible to Relative Energy Deficiency in Sport (RED-S), specifically low bone mineral density (BMD). Compared to sedentary groups, dancers have significantly higher BMD, but little is known about how BMD in dancers relates to other athletic populations. This knowledge may better inform comparative values and risk of bone injury. Objective: To evaluate associated factors of BMD among female dancers and sporting athletes. Design: Cross-sectional study. Setting: Human Performance Lab, University of Calgary. Patients (or Participants): 275 females [138 pre-professional dancers (18.4 years IQR: 15.3, 19.9); 137 recreational sport athletes (23.2 years IQR: 21.9, 24.7)] participated. Interventions (or assessment of risk factors): Factors evaluated:Age (years), BMI (kg/m 2 ), supplement intake (Ca+, vitD; yes/no), stress fracture history (yes/no), irregular menses (yes/no), and MRI/bone scan (yes/no), one-year injury history (yes/no), and activity (dance/sport). All two-way interactions were evaluated. Main outcome measurements: Whole-body BMD (g/cm 2 ) was estimated from dual-energy x-ray absorptiometry. Lower extremity (LE) segmentation followed published protocols. Results: The mean whole-body BMD was 1.03 g/cm 2 (SD:0.10) in dancers and 1.14 g/cm2 (SD:0.08) in athletes. LE BMD was 1.10 g/cm 2 (SD:0.11) in dancers and 1.19 g/cm2 (SD:0.08) in athletes. Age was positively associated with whole-body BMD (b=0.008, 97.5%CI;0.004, 0.012) and LE BMD (b=0.007, 97.5%CI;0.002, 0.010). Activity modified the relationship between BMI and BMD (p<0.001), for example, for a BMI of 20.1 kg/m 2 (mean of participants) the difference between dancers and athletes is -0.389 g/cm 2 [97.5% CI: -0.566, -0.195] and -0.381 g/cm 2 [97.5% CI: -0.552, -0.197] for whole body and LE BMD respectively. No other variables were associated with BMD. Conclusions: Older age is associated with higher BMD in female pre-professional dancers and sport athletes. The relationship between BMI and BMD depends on activity type for both whole-body and lower extremity sites. Efforts to prevent bone injury should focus on younger dancers and athletes and consider the associations of changing body composition over a training season with low BMD.